Guide to graduate study in economics and agricultural economics - Owen, Wyn F.; Antione, George H. (Colorado, United State : Economics Institute, 1977)
This guide provides prospective graduate students and their advisors with information on available graduate training programs in economics and agricultural economics offered at universities and colleges in the United States of America and Canada.
Includes bibliographical footnotes
ahz 09/04/2019
Loans
Keywords: Agricultural Economics; United States; Canada